Graphene quantum dots: Synthesis, characterization, cell viability, genotoxicity for biomedical applications - Behiye Şenel; Neslihan Demir; Gülay Büyükköroğlu; Mustafa Yıldız (Elsevier, 2019)
We report the synthesis and applications of a novel N-doped graphene quantum dots (GQDs) using hydrothermal reaction between citric acid and p-aminophenol. The synthesized N-doped GQDs have been characterized physico-chemically and evaluated its antioxidant, antimicrobial, DNA binding and cleavage activities. siRNA loading studies were performed and their effects on cells were evaluated. Obtained results indicate that monodisperse solution of N-doped GQDs has been obtained with particles size ca. ∼10.9 ± 1.3 nm. UV-Vis spectroscopy studies of the interactions between the N-doped GQDs and calf thymus DNA (CT-DNA) showed that the compound interact with CT-DNA via both intercalative and electrostatic binding. The DNA cleavage study showed that the N-doped GQDs cleaved DNA without any external agents. The antioxidant activity of N-doped GQDS was very active when compared to BHT. As the concentration of the compound increased, the antioxidant activity also increased. Cell viability assay demonstrated that the Ndoped GQDs showed cell viability (70%) when the concentration reached 200 μg/mL for A549 and also MDA-MB-231, 150 μg/mL for NIH-3T3 cell lines at 24 h incubation. N-doped GQDs were coated with Eudragit RS 100 and EphA2-siRNA was loaded. As a result of the studies on these formulations, it was concluded that there may be significant effects on A549 cells. The microscopy results revealed that N-doped GQDs was quickly internalized into the cell. Our novel N-doped-GQDs with siRNA are candidate for in situ tumor suppression via DNA and mRNA breakage. Keywords: N-doped Graphene quantum dots, DNA binding, DNA cleavage, DNA damage, Cell viability, siRNA uptake